Does Instructional Mode Alter the Effectiveness of a Curricular Response to Campus Sexual Violence?. (September 2022) - Johnson, Katherine M.; Liddell, Jessica L.; Lederer, Alyssa M.; Sheffield, Sydney
Online coursework is becoming a teaching and learning staple in higher education, especially since the onset of the COVID-19 pandemic. However, there is minimal literature regarding academic courses for campus sexual violence prevention, particularly comparing online versus face-to-face modalities. This study examined whether the effectiveness of a semester-long credit-bearing course (GESS 1900), designed to educate first year college students about correlates of sexual violence in order to ultimately reduce campus sexual violence, differed by instructional mode. Two cohorts had completed GESS 1900 in-person when the COVID-19 pandemic struck; the third cohort was taught entirely online through synchronous instruction and with the exact same faculty instructors and course materials. This created a natural experiment to compare outcomes by instructional mode. We used a quasi-experimental, pretest–posttest survey design to compare in-person ( n  = 92) versus online ( n  = 45) GESS 1900 students across eight previously validated attitudinal measures related to gender, sexuality, and sexual violence. Results from a two-way, mixed-factorial ANOVA showed no significant differences related to instructional mode on seven of the eight measures. Findings further showed change over time in the desired direction for all students, regardless of instructional mode; many measures showed different starting points for the two groups, but similar rates of change over time. Thus both in-person and synchronous online versions of GESS 1900 were effective in shaping positive student outcomes. The findings have important implications for educators seeking new or multiple delivery methods to educate college students about the pressing health concern of sexual violence.